The Characterization of Polysorbate. Issue 7 (20th July 2022) - Zhang, Sisi; Xiao, Hui; Li, Ning
Abstract: Polysorbates (PSs), including PS20 and PS80, are non‐ionic surfactants widely used in the pharmaceutical industry to enhance drug solubility and stability. Despite their wide application, PSs are prone to degradation by either hydrolysis or oxidation in drug formulations during storage; therefore, a PS characterization method assessing protein products is needed for stability testing and for understanding the degradation pathway. In this article, we detail our protocol for sample preparation for forced degradation study and our instrumentation setup for PS profiling and quantitation in protein samples. © 2022 Wiley Periodicals LLC. Basic Protocol 1 : Sample preparation for forced degradation of polysorbate in protein samples Basic Protocol 2 : Two‐dimensional liquid chromatography coupled with charged aerosol detector or mass spectrometry to analyze polysorbate degradation